2002
DOI: 10.1128/jcm.40.8.3044-3046.2002
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of West Nile Virus during Serologic Testing and Transport

Abstract: Inactivation of West Nile virus (WNV) in enzyme-linked immunosorbent assay (ELISA) wash buffer at 37°C was studied, as well as inactivation of WNV in cell culture medium over several days at an ambient temperature (28°C). Aliquots of WNV were removed from the 37°C ELISA wash buffer at 5, 15, 30, and 60 min for the former experiment, while daily aliquots of medium were sampled for the latter experiment. No virus was detected in the wash buffer at 30 and 60 min, while virus was readily detected from cell culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 3 publications
(1 reference statement)
0
22
0
Order By: Relevance
“…The recent spread of WNV is a case in point. A number of investigations have shown that WNV is rather labile and can be inactivated by simple methods (e.g., by lowering the pH and by detergent, pepsin, and heat treatment, respectively 28‐30 ). It was also described that WNV is sensitive to the alkylating agent PEN 110, which is used to inactivate pathogens in RBCs 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The recent spread of WNV is a case in point. A number of investigations have shown that WNV is rather labile and can be inactivated by simple methods (e.g., by lowering the pH and by detergent, pepsin, and heat treatment, respectively 28‐30 ). It was also described that WNV is sensitive to the alkylating agent PEN 110, which is used to inactivate pathogens in RBCs 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, inactivation of West Nile virus in a detergent-containing buffer has been demonstrated [16] . In our studies, we could verify a reduction in viral infectivity of at least 2 log scales after lysing infected cells with Nonidet P-40™-containing lysis buffer.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining sera yielded no plaques by 92 hours post-inoculation compared with plaques that developed ~65 hours post-inoculation from stock virus. Because RNA has been shown to be more stable than infectious virus through storage and shipping processes with variable temperature conditions or multiple freeze-thaw cycles, 51,52 we also tested samples by qRT-PCR. To obtain a result relevant to this study, we created a standard curve from plaque assay-quantified viremic mouse serum and expressed quantities of MAYV in test samples in terms of PFU equivalents based on the amount of RNA detected.…”
Section: Discussionmentioning
confidence: 99%